Tourist expectation and satisfaction towards pedestrian walkway in Georgetown, a World Heritage site - Mohd Noraffendi, Batrisyia Qistina; Abd Rahman, Nur Hidayah (IOP Publishing Ltd, 2020)
Recently, many cities in the world have incorporating walkability as a distinctive feature towards becoming a walkable tourism destination. A high-quality walkable environment has been greatly demanded by pedestrian use as it assures a sense of comfort and safety. In the context of Malaysia, the walkability concept is mostly applicable to any tourism places or the capital of a state long recognized as an urban heritage site. Despite this, there has been little research done in terms of the relationship between tourist expectation and tourist satisfaction towards walkability particularly in Georgetown, which is a World Heritage Site. The main objective of the study was to determine the relationship between tourist expectation and tourist satisfaction towards the existing pedestrian walkway in Georgetown. Research data were gathered via fieldwork observation and an online survey, whereby questionnaires were have distributed to 150 respondents made up of tourists who experienced walking in the study area. The outcomes demonstrated that tourist expectation in terms of the spatial features of the pedestrian walkway was relatively greater than tourist satisfaction. Hence, the findings of the study will be very useful for urban city planners in incorporating walkability to enhance the walking experience within the city.